Niche asymmetry of vascular plants increases with elevation. (16th April 2017) - Dvorský, Miroslav; Macek, Martin; Kopecký, Martin; Wild, Jan; Doležal, Jiří
Abstract: Aim: Species distributions along an environmental gradient are often not symmetric but skewed towards one end of the gradient. Various explanations for this skewness have been proposed but the patterns of niche asymmetry along extensive environmental gradients have been rarely explored. In this study, we tested three predictions of asymmetric abiotic stress limitation (AASL) hypothesis that predicts a steeper decrease in the probability of occurrence towards the more stressful end of a plant distributional range. Location: Ladakh, arid Himalayas, where drought stress dominates in the lower elevation, whilst the cold stress dominates in the upper elevations. Methods: Using data from 4062 plots (2640–6150 m a.s.l.), we explored the shapes of response curves of 395 vascular plant species through Huisman‐Olff‐Fresco models. We compared the observed patterns of niche asymmetry along the elevational gradient with null models. Results: Species with symmetric response curves (61.5%) prevailed at lower elevations, whilst species with left‐skewed responses (36.2%) were significantly underrepresented up to 3750 m a.s.l. and occurred significantly more frequently at 5150–5450 m a.s.l. Right‐skewed responses were rare (2.3%) along the whole gradient. The steepness of the response increased with elevation. Response types were found in similar proportions across different habitats and functional groups. Main conclusions: Our results support the predictions of AASL hypothesis for cold limits, but not for dry limits. The low proportion of right‐skewed responses over the entire gradient suggests an effective adaptation of the local flora to arid conditions, or sufficient opportunity to avoid drought stress through the presence of favourable habitat patches. The accumulation of skewed responses at high elevations likely reflects shared physiological limits of many steppe species, whose distribution abruptly ends at the transition between steppe and alpine zones. Cold, therefore, represents a stronger barrier to species distribution than drought.